2020
DOI: 10.3389/fpubh.2020.595348
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative SARS-CoV-2 Antibody Screening of Healthcare Workers in the Southern Part of Kyoto City During the COVID-19 Pre-pandemic Period

Abstract: Background: The coronavirus disease-2019 (COVID-19) pandemic is associated with a heavy burden on the mental and physical health of patients, regional healthcare resources, and global economic activity. While understanding of the incidence and case-fatality rates has increased, there are limited data concerning seroprevalence of antibodies against the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) in healthcare workers during the pre-pandemic period. This study aimed to quantitatively evaluate se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Currently, the seroprevalence of SARS‐CoV‐2 antibodies was reported to be 0.07%–6.25% among HCWs in Japan. 5 , 6 , 7 , 8 , 9 , 10 These studies also showed that the seroprevalence in HCWs did not differ between high‐ and low‐risk groups. Since seroprevalence largely depends on the assays used, we performed four assays to facilitate comparison with other studies.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Currently, the seroprevalence of SARS‐CoV‐2 antibodies was reported to be 0.07%–6.25% among HCWs in Japan. 5 , 6 , 7 , 8 , 9 , 10 These studies also showed that the seroprevalence in HCWs did not differ between high‐ and low‐risk groups. Since seroprevalence largely depends on the assays used, we performed four assays to facilitate comparison with other studies.…”
Section: Discussionmentioning
confidence: 67%
“…Indeed, SARS‐CoV‐2 infection of HCWs who work in endoscopy units was found to be 4.3% (42/968) in Northern Italy, an endemic area, 3 and 14% (10/73) in Egypt, where the cumulative number of patients with COVID‐19 was equivalent to that of Japan. 4 Although the seroprevalence of SARS‐CoV‐2 antibodies among HCWs was reported to be 0.07%–6.25% in Japan, 5 , 6 , 7 , 8 , 9 , 10 there are few data on the seroprevalence of SARS‐CoV‐2 antibodies among HCWs in endoscopy units. This study was undertaken to investigate the seroprevalence of SARS‐CoV‐2 antibodies among HCWs who practice and support gastrointestinal endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…28 Whilst NAATs are capable of diagnosing current infection, antibody testing identifies exposure to the pathogen over the patient's lifetime, supporting diagnosis later during the disease course. 29 Antibody testing aids our understanding of COVID-19 and our immune response, [30][31][32][33] the spread of infection, 14,[34][35][36] and, more recently, our response to vaccine administration and long-term efficacy. 37…”
Section: Available Classes Of Diagnostic Testsmentioning
confidence: 99%
“…While NAATs are capable of diagnosing current infection, antibody testing identifies exposure to the pathogen over the patient’s lifetime, supporting diagnosis later during the disease course [ 30 ]. Antibody testing aids our understanding of SARS-CoV-2 infection and our immune response [ 31–34 ], the spread of infection [ 14 , 35–37 ], and, more recently, our response to vaccine administration and long-term efficacy [ 38 ]. However, as there is a delay between infection and antibody development and the presence of antibodies following recovery from infection is anticipated, recent guidance notes that antibody testing does not replace virologic testing to establish the presence or absence of acute SARS-CoV-2 infection in the majority of settings [ 39 ].…”
Section: Introductionmentioning
confidence: 99%